The complexation of Cm(III) with succinate studied by time-resolved laser fluorescence spectroscopy and quantum chemical calculations - Fröhlich, Daniel R.; Trumm, Michael; Skerencak-Frech, Andrej; Panak, Petra (Inorganic chemistry, 2016)
The complexation of Cm(III) with succinate in an aqueous NaCl solution was studied as a function of ionic strength, ligand concentration, and temperature using time-resolved laser fluorescence spectroscopy (TRLFS). After the Cm(III) speciation was determined by peak deconvolution, the temperature-dependent thermodynamic stability constants (log Kn0(T)) were determined for the stepwise formation of [CmSucn]3-2n (n = 1-3) in the temperature range 20-80 °C (n = 3 only when T ≥ 50 °C) using the specific ion interaction theory (SIT). The first and second complexation steps show an endothermic behavior, as the respective standard reaction enthalpies (ΔrHm0) and entropies (ΔrSm0) derived from the integrated van’t Hoff equation are positive. These TRLFS results are complemented by quantum chemical calculations to resolve the molecular structure of the formed Cm(III) complexes. The results show that the formation of a seven-membered chelate ring is the favored conformation of [CmSucn]3−2n (n = 1−3).
Gesehen am 19.06.2020